2005
DOI: 10.1016/j.femsle.2005.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of class 1 integrons-mediated antibiotic resistance among calf pathogenic Escherichia coli

Abstract: Escherichia coli isolates from calf diarrhea cases (n=22) in the Beijing surrounding region in China were characterized for disease serotype, virulence factors, antimicrobial susceptibility pattern and class 1 integrons. 59% (n=13) of the isolates were positive for the int I1 gene. The presence and genetic content of class 1 integrons in 13 E. coli isolates were examined by PCR and sequencing. Sequencing analysis revealed six gene cassettes, which encoded resistance to trimethoprim (dfrA1, dfrA17), aminoglycos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 15 publications
(19 reference statements)
3
15
1
Order By: Relevance
“…Other studies from Asia and Europe have demonstrated a similar range (17%-64%) of prevalence of class 1 integrons from clinical and animal bacterial isolates, but the allelic sequences of their gene cassettes were not compared [19][20][21][22][23]. Our results reveal not only the high prevalence of integronmediated drug resistance but also the high frequency of aadA and dfrA gene cassettes that are identical in sequence in human, animal, and environmental isolates.…”
Section: Discussionsupporting
confidence: 50%
“…Other studies from Asia and Europe have demonstrated a similar range (17%-64%) of prevalence of class 1 integrons from clinical and animal bacterial isolates, but the allelic sequences of their gene cassettes were not compared [19][20][21][22][23]. Our results reveal not only the high prevalence of integronmediated drug resistance but also the high frequency of aadA and dfrA gene cassettes that are identical in sequence in human, animal, and environmental isolates.…”
Section: Discussionsupporting
confidence: 50%
“…Furthermore, it is noteworthy that the same dfrA17-aadA5 integron appears to be common in E. coli and Salmonella spp. isolated from chickens, livestock, and water (1,6). We have also recently found that one of the six CgA animal isolates (a 1999 cow isolate) reported by Tartof et al as ST101 (33) contains this dfrA17-aadA5 integron arrangement, with 100% sequence identity.…”
Section: Discussionmentioning
confidence: 77%
“…According to the previous studies, there are several reports related to the rates of antimicrobial resistance in isolates of animal origin worldwide (11)(12)(13)(14)(15). Broad use of antimicrobials in agriculture selects for resistant bacteria that may enter the food chain, and potentially result in foodborne disease in humans that is less responsive to treatment with conventional antibiotics (16).…”
Section: Introductionmentioning
confidence: 99%